The Effect of Environmental Pressures and the Covid19 Pandemic on the Adoption of TikTok by MSMEs: Can MSME Engagement Moderate? - Religia, Yoga (Journal of International Conference Proceedings, 2022)
This study aims to review the adoption of TikTok social media by MSMEs during a Covid19 pandemic within the scope of the organization. The integration of environmental factors within the framework of TOE, environment during a pandemic, and MSME engagement was carried out to explain the key parameters in explaining TikTok's social media dopsi. This research was conducted by distributing a survey to 200 respondents who are MSMEs in the Special Region of Yogyakarta Indonesia affected by Covid19 who have used the TikTok application. Based on the questionnaire distributed only 155 survey results can be used for later analysis using SEM-PLS. The test results showed that customer pressure had no significant effect on the adoption of TikTok social media by MSMEs. Competitive pressures, the environment during a Covid19 pandemic, and MSME engagement have positively significantly affected the adoption of TikTok social media by MSMEs. The study found that the role  of MSME engagement in moderating customer pressure and competitive pressure on TikTok's social media adoption is simply a predictor moderation. In addition, it is also known that MSME engagement can positively significantly moderate the environment during a Covid19 pandemic to the adoption of TikTok social media.